2007
DOI: 10.1007/s11434-007-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Attentional modulation of motion-induced blindness

Abstract: When a global moving pattern is superimposed on high-contrast stationary or slowly moving stimuli, the stimuli can be perceived as disappearing and reappearing alternately for periods of several seconds. This visual illusory phenomenon was named "motion-induced blindness" (MIB) in recent literature. So far there is no consensus on the mechanism of MIB, especially on the role of attention in this phenomenon. To examine the effect of spatial attention on MIB, the present study manipulated the participants' spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 28 publications
6
29
0
Order By: Relevance
“…The most frequently used display for demonstrating MIB consists of three yellow targets and a blue mask of rotating crosses, originally introduced by Bonneh and colleagues (2001). Using this display, various stimulus parameters have been studied (Bonneh et al, 2001;Hsu, Yeh and Kramer, 2004;Metzger, 2009;Mitroff & Scholl, 2005;Sakaguchi, 2006;Schölvinck & Rees, 2009;Shibata, Kawachi & Gyoba, 2010), among which are the effect of target location (Geng, Song, Li, Xu & Zhu, 2007;Nuruki, Oliver, Campana, Wash & Rothwell, 2013;Rosenthal, Davies, Aimola-Davies, & Humphreys;Schölvinck & Rees, 2009;Wells, Leber & Sparrow, 2011;Wallis & Arnold, 2009), mask speed (Bonneh et al, 2001;Grindley & Townsend, 1965;Libedinsky et al, 2009), and cues of mask depth (Graf, Adam & Lages, 2002;Rosenthal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently used display for demonstrating MIB consists of three yellow targets and a blue mask of rotating crosses, originally introduced by Bonneh and colleagues (2001). Using this display, various stimulus parameters have been studied (Bonneh et al, 2001;Hsu, Yeh and Kramer, 2004;Metzger, 2009;Mitroff & Scholl, 2005;Sakaguchi, 2006;Schölvinck & Rees, 2009;Shibata, Kawachi & Gyoba, 2010), among which are the effect of target location (Geng, Song, Li, Xu & Zhu, 2007;Nuruki, Oliver, Campana, Wash & Rothwell, 2013;Rosenthal, Davies, Aimola-Davies, & Humphreys;Schölvinck & Rees, 2009;Wells, Leber & Sparrow, 2011;Wallis & Arnold, 2009), mask speed (Bonneh et al, 2001;Grindley & Townsend, 1965;Libedinsky et al, 2009), and cues of mask depth (Graf, Adam & Lages, 2002;Rosenthal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of target location, a number of studies have reported greater disappearance when a target is located in the upper left quadrant of the visual display, compared to other 3 tested locations (Bonneh et al, 2001;Nuruki et al, 2013;Rosenthal et al, 2013;Wells & Leber, 2014;Wells et al, 2011). A more frequent disappearance of upper left targets has been replicated several times (Bonneh et al, 2001;Geng et al, 2007;Grindley & Townsend, 1965;Rosenthal et al, 2013). However, research finding a significant upper left bias generally uses the original three target triangular display (Bonneh et al, 2001), and finds a significant bias only in relation to the lower central target (Bonneh et al, 2001;Nuruki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies demonstrated a link between miscrosaccades and shifts in visual attention (Hafed, 2013;Hafed, Goffart, & Krauzlis, 2009;Yuval-Greenberg, Merriam, & Heeger, 2014). Whereas attention modulates illusory disappearances in MIB, TE, and PFI in the same fashion (Devyatko, 2011;De Weerd et al, 2006;Geng et al, 2007;Lou, 1999;Scho¨lvinck & Rees, 2009), the mechanism producing similar patterns of microsaccades in the three illusions can be also modulated by shifts in attention.…”
Section: Discussionmentioning
confidence: 96%
“…MIB may be enhanced for especially high-contrast anomalous targets, fast mask speeds, and high-quality mask motion (Bonneh et al, 2001) because these factors all enhance the magnitude of the contrast between the mask and the target, thus enhancing the anomaly itself. MIB may be enhanced by attention to the targets (Carter, Luedeman, Mitroff, & Nakayama, 2008;Geng, Song, Li, Xu, & Zhu, 2007) for a similar reason: Such attention may serve to highlight the underlying conflict, whereas unattended targets may already go unnoticed without such effort, even without inducing a perceptual scotoma. At the same time, MIB may be enhanced for especially lowcontrast anomalous targets (Hsu et al, 2004) because such targets provide relatively little bottom-up stimulation (constituting an anomaly that must then be explained away) in the first place.…”
Section: Discussionmentioning
confidence: 99%